2006
DOI: 10.1007/s00192-006-0250-3
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the anatomy of oncologic postradiation vesicovaginal fistulae with reconstructed computed tomography

Abstract: The key diagnosis and treating of vesicovaginal fistulae is accurate imaging. We illustrate the latest use of enhanced computed tomography for such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Cross-sectional imaging techniques, such as CT and MRI, play an increasingly important role and are frequently implemented in complicated cases. With the development and emerging utilization of MDCT in everyday clinical practice in the past decade, it has been found to be a sensitive and specific technique in the detection and precise anatomic delineation of these rare pathologic abnormalities [6], its main advantages being its maximal spatial and temporal resolution. However, to our knowledge, there is no large study to date that has compared MDCT with alternative imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional imaging techniques, such as CT and MRI, play an increasingly important role and are frequently implemented in complicated cases. With the development and emerging utilization of MDCT in everyday clinical practice in the past decade, it has been found to be a sensitive and specific technique in the detection and precise anatomic delineation of these rare pathologic abnormalities [6], its main advantages being its maximal spatial and temporal resolution. However, to our knowledge, there is no large study to date that has compared MDCT with alternative imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, urogenital fistulas were explored by excretory urography or retrograde cystography [4,5]. With the evolution of CT and the emerging utilization of MDCT in everyday clinical practice, it has been found that MDCT is a more sensitive and specific technique in the detection and precise anatomic delineation of these rare pathologic abnormalities compared with conventional radiology modalities [6,7]. Moving one step forward, we initiated a new protocol combining CT cystography and intravaginal neutral contrast agent.…”
mentioning
confidence: 99%
“…In a retrospective review of 20 cases of proved Three-dimensional CT reconstructions of complex colovaginal and vesicovaginal fistulas help identify the precise course of the fistulous tract and provide the detailed anatomic views the surgeon needs for preoperative planning (13,14). Lawrentschuk et al (14) described the case of a vesicovaginal fistula in a patient who previously had undergone a radical hysterectomy and radiation therapy for uterine adenocarcinoma. Findings at vaginal examination and cystoscopy were involved loop of small bowel.…”
Section: Ct Examinationmentioning
confidence: 98%
“…indicative of the presence of a fistula but failed to reveal the precise site. Multidetector CT cystography with three-dimensional reconstructions helped confirm the presence of a fistula and precisely delineated the tract (14).…”
Section: Ct Examinationmentioning
confidence: 99%